Construction of Organic‐Rich Solid Electrolyte Interphase for Long‐Cycling Lithium–Sulfur Batteries - Li, Zheng; Li, Yuan; Bi, Chen‐Xi; Zhang, Qian‐Kui; Hou, Li‐Peng; Li, Xi‐Yao; Ma, Jin; Zhang, Xue‐Qiang; Li, Bo‐Quan; Wen, Rui; Zhang, Qiang (Advanced functional materials, 2024)
Lithium–sulfur (Li–S) batteries promise great potential as high‐energy‐density energy storage devices. However, the parasitic reactions between lithium polysulfides (LiPSs) and Li metal anodes render limited cycling lifespan of Li–S batteries. Herein, an organic‐rich solid electrolyte interphase (SEI) is constructed to inhibit the LiPS parasitic reactions and achieve long‐cycling Li–S batteries. Concretely, 1,3,5‐trioxane is introduced as a reactive co‐solvent that decomposes on Li anode surfaces and contributes organic components to the SEI. The as‐constructed organic‐rich SEI effectively inhibits the LiPS parasitic reactions and protects working Li metal anodes. Consequently, the cycling lifespan of Li–S coin cells with 50 µm Li anodes and 4.0 mg cm−2 sulfur cathodes is prolonged from 130 to 300 cycles by the organic‐rich SEI. Furthermore, the organic‐rich SEI enables a 3.0 Ah‐level Li–S pouch cell to achieve a high energy density of 400 Wh kg−1 and stable 26 cycles. This study affords an effective organic‐rich SEI to inhibit the LiPS parasitic reactions and inspires rational SEI design to achieve long‐cycling Li–S batteries. A robust organic‐rich solid electrolyte interphase (SEI) is constructed to inhibit the lithium polysulfide parasitic reactions and achieve long‐cycling lithium–sulfur batteries. The organic‐rich SEI constructed by the decomposition of 1,3,5‐trioxane effectively protects lithium metal anodes during cycling while the routine SEI induces inhomogeneous lithium deposition and rapid lithium anode failure.